Implementasi Metode MOORA Penentuan Pusat Perbelanjaan Terbaik Di Riau - Hardianto, Roki; Yunefri, Yogi; Wirdahchoiriah; Wiza, Fana; Filtri, Heleni (The Indonesian Journal of Computer Science, 2022)
This research has motivated by an increasing number of shopping centers that appear in the community with various offers and products. The quality of mall services and facilities determines the target audience in measuring the quality of shopping centers. The purpose of this research is to help developers improve the quality of services and more. Therefore, a Decision Support System is needed to assist the assessment process using five alternatives and seven criteria. The method used is Multi-Objective Optimization on the Ratio Analysis (MOORA) basis. The results showed that the Living World mall was chosen as the best mall in the city of Pekanbaru with a final point of 3.17.